The life and times of Nicolas Dutot - François R. Velde (Federal Reserve Bank of Chicago, 2009)
Nicolas Dutot (1684-1741) is an important figure for the history of economic thought, as a pioneer in monetary theory and price statistics, and for economic history as a chronicler of John Law's System. Yet until recently very little about him was known, some of it incorrect. I present extensive research that reveals a remarkable career rising from humble origins and full of surprises. He spent his formative years in the ranks of the 'ancienne finance' he was thought to despise, and then worked for the chamber of justice that he so decried in his writings, only to be sent to the Bastille for corruption. After working for Law's Bank and retiring quite comfortably thereafter, he continued to socialize with his pre-System financier and banker friends, joined a short-lived learned society, and accumulated a substantial library that reveals much about his tastes and affinities. The portrait that emerges is at odds with the image of an honest accountant he tried to project, but also richer and more engaging.
Keywords: B11; B31; N43; 330; Dutot; biography; early monetary theory; history of price indices; pre-classical economic thought